Pengembangan Objek Wisata Alam Lejja Dalam Meningkatkan Pendapatan Retribusi Wisata Di Dinas Pariwisata, Kepemudaan Dan Olahraga Kabupaten Soppeng - Umar, Muhammad Hidayat; Sudarmi, Sudarmi; Riskasari, Riskasari (Universitas Muhammadiyah Makassar, 2021)
This study aimed to provide an overview and explanation of Lejja Natural Tourism Development in Increasing the Revenue of Tourism Levies in the Tourism, Youth and Sports Office of Soppeng Regency. This study used the type of qualitative descriptive research. Data collection techniques were observation and interviews with informants. Data analysis used an interactive analysis model. The results of the study showed that the development of the natural tourism object was not fully well done by the Department of Tourism, Youth and Sports in terms of tourism object development. This was seen from the aspects of (1) the criteria of attracting tourists (attractions), (2) the criteria for developing tourist areas, (3) the criteria for community welfare. Supporting factors in this activity included Beautiful Natural Panorama, Cool and still original or natural, abundant hot springs, and good security conditions. While the limiting factor was the limited budget for the cost of facilities and infrastructure that were still inadequate attractions.